Biopsy samples from patients with irritable bowel syndrome, but not from those with mastocytosis or unspecific gastrointestinal complaints reveal unique nerve activation in all gut regions independent of mast cell density, histamine content or specific gastrointestinal symptoms - Vignali, Sheila; Buhner, Sabine; Greiter, Wolfgang; Daniel, Hannelore; Frieling, Thomas; Schemann, Michael; Annahazi, Anita (Frontiers in Neuroscience, 2024)
Introduction We previously showed enteric nerve activation after application of colonic mucosal biopsy supernatants from patients with irritable bowel syndrome (IBS). The question remains whether this is a region-specific or a generalized sensitization. We tested the nerve-activating properties of supernatants from large and small intestinal regions of IBS patients with diarrhea (IBS-D) in comparison to those from mastocytosis patients with diarrhea (MC-D) or non-IBS/non-MC patients with GI-complaints. MC-D patients were included to test samples from patients with an established, severe mast cell disorder, because mast cells are suggested to play a role in IBS. Methods Voltage-sensitive dye imaging was used to record the effects of mucosal biopsy supernatants from IBS-D, MC-D, and non-IBS/non-MC on guinea pig submucous neurons. Mast cell density and histamine concentrations were measured in all samples. Results The median neuroindex (spike frequency × % responding neurons in Hz × %) was significantly (all p < 0.001) increased for IBS-D (duodenum and colon, proximal and distal each, 49.3; 50.5; 63.7; 71.9, respectively) compared to non-IBS/non-MC (duodenum and colon, proximal and distal each, 8.7; 4.9; 6.9; 5.4, respectively) or MC-D supernatants (duodenum and colon, proximal and distal each, 9.4; 11.9; 0.0; 7.9, respectively). Nerve activation by MC-D and non-IBS/non-MC supernatants was comparable (p>0.05). Mast cell density or histamine concentrations were not different between IBS-D, MC-D, and non-IBS/non-MC samples. Discussion Nerve activation by biopsy supernatants is an IBS hallmark that occurs throughout the gut, unrelated to mast cell density or histamine concentration. At least as important is our finding that GI complaints per se were not associated with biopsy supernatant-induced nerve activation, which further stresses the relevance of altered nerve behavior in IBS.